KARAKTERISASI BRIKET KULIT KAYU GALAM DAN CANGKANG BIJI KARET DENGAN VARIASI KOMPOSISI DAN PEREKAT GETAH DAMAR PADA PENCELUPAN MINYAK JELANTAH - Damayanti, Dian Khatimah; Annisa, Nova; Haryanti, Ninis Hadi; Prihatini, Nopi Stiyati; Nilawati, Indah Nirtha (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Biomass energy can be used as a substitute for petroleum fuel (fossil) by converting it into briquettes which have a high calorific value. The aim of the study was to analyze the effect of variations in the composition of raw materials on the characteristics of the waste briquettes of galam bark and rubber seed shells in used cooking oil immersion. The independent variables in this study were variations in the composition of raw material for galam bark waste: rubber seed shell, namely 70%: 30%; 60%:40%; 50%:50%; 40%:60%; 30%:70%, and control variations of galam bark:rubber seed shell, namely 100%:0% and 0%:100%. The particle size of galam bark charcoal and rubber seed shell was 60 mesh, pressure was 200 kg/cm2 and resin adhesive was 9%. The best composition variation is 40% Galam bark and 60% rubber seed shell with a calorific value of 8006 cal/gr, 3.1% moisture content, 2.98% ash content, 84.26% volatile content, and 10.24 compressive strength. kg/cm2.